Effectiveness of the prevention of mother-to-child transmission (PMTCT) policy in the Northern Cape, South Africa - Myburgh, Bianca (University of the Free State, 2015)
Introduction Human Immunodeficiency Virus (HIV) infection in children is mainly caused by Mother-to-Child Transmission (MTCT). The Prevention of Mother-to-Child Transmission (PMTCT) policy has been implemented in South Africa to reduce the rate of MTCT. Even though this policy has been in place for more than ten years and despite the reduction in MTCT, the challenge remains to eliminate MTCT completely. This study investigates the factors that may influence the effectiveness of the PMTCT policy. Methods Four clinics in the Frances Baard District, South Africa, where PMTCT services are rendered were included. A hundred mothers-child-pairs, where the mother is HIV infected and breastfed her child, but has stopped breastfeeding and the six week post cessation of breastfeeding HIV test was done on child, were included in the study. A questionnaire was completed by the researcher during an interview with the mother and anthropometric measurements of both mother and child were taken. The clinic files of mothers were also used to collect data. Ethical approval to conduct this study was obtained from the Ethics Committee, Faculty of Health Sciences, University of the Free State and the Northern Cape Department of Health Research Ethics Committee. Mothers provided informed consent before interviews were conducted. The Department of Biostatistics, University of the Free State performed the statistical analysis of data. Results All mothers included in this study attended antenatal clinics. Mothers who were not known to be HIV infected were tested antenatal and CD4 cell counts and HIV stages were indicated in all files. Twenty two mothers visited the antenatal clinic less than four times as recommended and 23 mothers visited for the first time during their third trimester. Only one mother reported that she received no counselling on feeding practises, and even though mothers were mostly knowledgeable about feeding practices, only 58 mothers introduced solids at the correct age and 31 mothers mixed fed their children.The number of counselling sessions did not affect breastfeeding duration (95% CI: [-2; 3]) or the age of introduction of solids (95% CI:[-2; 1]) Knowledge about MTCT was poor as most mothers (82%) only knew that MTCT could occur during breastfeeding. Younger mothers were more knowledgeable (95% CI: [0.17; 5.56]). The number of counselling sessions did not affect the knowledge of the mother (p=0.12). Five children and eight mothers never started with any antiretroviral therapy (ART). Thirteen children and 27 mothers defaulted their ART treatment. No children tested HIV infected at six weeks but three children tested HIV infected at the 18 month test. Mothers with HIV infected children had a more advanced stage of HIV infection (95% CI: [23.5%; 87.1%]), lower CD4 cell count (p=0.03) and defaulted their ART during breastfeeding (95% CI: [21.5%; 85.4%]) compared to mothers with HIV uninfected children. All three children that tested HIV infected were of mothers with Stage 2 HIV infection, with a CD4 cell count of less than 350 cells/mmᶾ and defaulted their ART during breastfeeding. Conclusions and recommendations Using the 2010 and 2013 PMTCT policies as benchmark, the PMTCT programme is implemented relatively well in this district although improvements still need to be made. The knowledge of the mothers about feeding practices and MTCT should be addressed by means of counselling by properly informed health care professionals. Missed opportunities for training resulted, as mothers did not attend antenatal clinic as soon and as often as recommended. Mothers should be motivated to improve ART adherence as this can affect CD4 cell count and HIV progression, all factors that contributed to MTCT. Counselling should be focussed on ART adherence and MTCT. Shortages of ART at clinics should be addressed to eliminate this reason for ART defaulting. All women of childbearing age should also be made aware of the importance of early antenatal attendance. The rate of HIV transmission in this district is below the national reported rate but it remains a challenge to eliminate MTCT completely.

Menslike Immuniteitsgebrek Virus (MIV) infeksie in kinders kan grootliks toegeskryf word aan Moeder-na-Kind Oordrag (MNKO). Die Voorkoming van Moeder na Kind Oordrag (VMNKO) beleid is geïmplementeer in Suid Afrika om MNKO teverlaag. Hierdie beleid is al langer as tien jaar geïmplementeer, maar alhoewel MNKO verminder het, bly die uitdaging om MNKO totaal uit te skakel. Hierdie studie stel ondersoek in na die faktore wat moontlik die effektiwiteit van die VMNKO beleid kan beïnvloed Metode Vier klinieke in die Fraces Baard Distrik, Suid Afrika waar VMNKO dienste gelewer word is ingesluit in die studie. ‘n Honderd moeder-kind pare, waar die ma MIV besmet is en haar kind geborsvoed het, maar opgehou borsvoed het en die ses weke MIV toets na die staking van borsvoeding uitgevoer is op die kind, is ingesluit by hierdie studie. ‘nVraelys is deur die navorser tydens ‘n onderhoud met die moeder voltooi en antropometriese metings van beide moeder en kind is geneem. Die kliniek lêers van ma’s is ook gebruik om data te versamel. Etiesegoed keuring om die studie uit te voer is vanaf die Etiekkomitee, Fakulteit Gesondheidswetenskappe van die Universiteit van die Vrystaat asook die Noord-Kaap Departement van Gesondheid se Navorsingsetiekkomitee ontvang. Alle ma’s het ingeligte toestemming verleen voordat die onderhoude gevoer is. Die Departement Biostatistiek, Universiteit van die Vrystaat het die statistiese ontleding van die data gedoen. Resultate Al die ma’s in die studie het die voorgeboorte kliniek bygewoon. Al die ma’s met onbekende HIV status is tydens die kliniek besoek getoets en CD4 sel telling en HIV stadium is in alle leers aangedui. Twee en twintig ma’s het die voorgeboortekliniek minder as die voorgestelde vier keer besoek en 23 ma’s het die kliniek vir die eerste keer tydens hul derde trimester besoek. Slegs een ma het aangedui dat sy geen onderrig by die kliniek aangaande voiding ontvang het nie. Al het ma’s redelike kennis oor voiding praktyke getoon, het slegs 58 ma’s vaste kosse op die regte ouderdom ingesluit en 31 ma’s het gemengde voedings gegee. Die hoeveelheid onderrig sessies wat die ma ontvang het, het nie die duur van borsvoeding (95% CI: [-2; 3]) of die ouderdom waarop vaste voedsel ingesluit is (95% CI:[-2; 1]) beïnvloed nie. Kennis oor MNKO was swak en die meeste ma’s kon net aandui dat MNKO deur borsvoeding geskied. Jonger ma’s het meer kennis gehad (95% CI: [0.17; 5.56]). Die hoeveelheid onderrig sessies het nie die kennis van die ma’s beïnvloed nie (p=0.12). Vyf kinders en agt moeders het nooit op enige antiretrovirale terapie (ART) begin nie. Dertien kinders en 27 ma’s het versuim om hul ART daagliks te neem. Geen kinders het MIV besmet getoets op ses weke nie, maar drie kinders was MIV besmet tydens die 18 maande toets. Ma’s met MIV besmette kinders het ‘n meer gevorderde MIV stadium gehad (95% CI: [23.5%; 87.1%]), ‘n laer CD4 sel telling (p=0.03) en het hul ART versuim tydens borsvoeding (95% CI: [21.5%; 85.4%]) in vergelyking met ma’s met MIV onbesmette kinders. Al drie MIV besmette kinders se moeders het ‘n MIV stadium van 2 gehad, ‘n CD4 sel telling van minder as 350 selle/mmᶾ en het hul ART versuim tydens borsvoeding. Gevolgtrekking en aanbevelings In vergelyking met die 2010 en 2013 VMNKO beleid is die VMNKO program relatief goed geïmplementeer in die distrik alhoewel daar steeds verbetering aangebring kan word. Kennis van ma’s aangaande voedingspraktyke en MNKO sal moet verbeter deur onderrig deur behoorlik opgeleide gesondheidsorgwerkers. Geleenthede vir opleiding is verbeur, aangesien ma’s nie voorgeboorte klinieke so vroeg en gereeld as aanbeveel besoek het nie. Ma’s moet veral onderrig word oor die gebruik van ART soos voorgeskryf, wat hul CD4 sel telling en MIV stadium beïnvloed, aangesien hierdie faktore bygedra het tot MNKO. Onderrig moet op ART nakoming en MNKO toegespits word. Tekorte van ART by klinieke moet aangespreek word aangesien dit gedeeltelik verantwoordelik was vir ART versuiming. Alle vroue moet bewusgemaak word oor die belangrikheid van vroeë voorgeboorte kliniek besoeke. Die MNKO koers in hierdie distrik is laer as die gerapporteerde nasionale koers, maar dit bly ‘n uitdaging om MNKO totaal uit te skakel.
Dissertation (M.Sc. (Nutrition and Dietetics)--University of the Free State, 2015
Keywords: Human Immunodeficiency Virus (HIV); Acquired Immunodeficiency Syndrome (AIDS); Prevention of Mother-to-Child Transmission (PMTCT); Mother-to-Child Transmission (MTCT); Anthropometry; Breastfeeding; Risk factors; Antiretroviral Therapy (ART); Social Grants; AIDS (Disease) -- Prevention -- South Africa -- Northern Cape; Mother and infant; Antiretroviral agents -- Therapeutic use; HIV infections -- Prevention -- South Africa -- Northern Cape